2015
DOI: 10.1113/jphysiol.2014.284869
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shifts, vasodilatation and ambulatory blood pressure reduction during long duration spaceflight

Abstract: Key pointsr Weightlessness in space induces initially an increase in stroke volume and cardiac output, accompanied by unchanged or slightly reduced blood pressure.r It is unclear whether these changes persist throughout months of flight. r Here, we show that cardiac output and stroke volume increase by 35-41% between 3 and 6 months on the International Space Station, which is more than during shorter flights.r Twenty-four hour ambulatory brachial blood pressure is reduced by 8-10 mmHg by a decrease in systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
160
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 50 publications
(149 reference statements)
20
160
4
Order By: Relevance
“…The 10.9% Hb reduction matched with the 10% plasma volume loss previously measured in space, 1,8,10,11 suggesting that Hb regulation in space replicates earthly Hb levels. Therefore, the 10.9% Hb reduction we reported in astronauts returning from missions averaging 145 days may represent the completed human erythrocytic adaptation; the new "space normal".…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The 10.9% Hb reduction matched with the 10% plasma volume loss previously measured in space, 1,8,10,11 suggesting that Hb regulation in space replicates earthly Hb levels. Therefore, the 10.9% Hb reduction we reported in astronauts returning from missions averaging 145 days may represent the completed human erythrocytic adaptation; the new "space normal".…”
Section: Resultssupporting
confidence: 76%
“…[2][3][4] However, 31 astronauts had normal Hb during 180-day missions onboard the International Space Station (ISS), seemingly contradicting the hypothesis that space flight leads to anemia. 8,9 This blood volume redistribution rapidly reduces plasma volume by 10%. 5,6 The study of anemia during and after spaceflight is complicated by the diagnostic criteria for anemia that are based on Hb concentration, a quantity affected by both changes in plasma volume and changes in RBC mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations showed that the baroreflex sensitivity fluctuates along with altered blood volume distribution [1, 2, 3], which affects neural mechanisms involved in dynamic cardiovascular coordination. Several reports indicate that heart rate is maintained at preflight values [4, 5, 6] and that parasympathetic activity is reduced [4] in space. Cardiac output and stroke volume are reportedly increased in space as a result of an increase in preload to the heart induced by upper body fluid shift from the lower body segments with no major difference in sympathetic nerve activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that heart rate is maintained at preflight values [4, 5, 6] and that parasympathetic activity is reduced [4] in space. Cardiac output and stroke volume are reportedly increased in space as a result of an increase in preload to the heart induced by upper body fluid shift from the lower body segments with no major difference in sympathetic nerve activity [6]. However, high sympathetic nervous activity, measured invasively by microneurography in peroneal nerves, has been simultaneously detected in space in three astronauts [7] compared to the ground-based supine posture.…”
Section: Introductionmentioning
confidence: 99%